Comparison of fingolimod and dimethyl fumarate in the treatment of multiple sclerosis: Two-year experience. Issue 3 (August 2017) - Vollmer, Brandi; Nair, Kavita V; Sillau, Stefan H; Corboy, John; Vollmer, Timothy; Alvarez, Enrique
Background: Fingolimod (FTY) and dimethyl fumarate (DMF) are multiple sclerosis (MS) oral therapies that became available in 2010 and 2013, respectively. Objective: The objective of this article is to compare discontinuation rates, efficacy, and adverse events (AEs) of FTY and DMF over two years. Methods: Patients prescribed FTY or DMF at the Rocky Mountain MS Center at University of Colorado prior to October 2013 were identified. Clinician-reported data were retrospectively collected. Primary outcome was discontinuation of drug by the end of year two. Reasons for discontinuation were evaluated. Results: A total of 271 FTY and 342 DMF patients were evaluated. Patients had a mean age of 42.5 (FTY) and 45.8 (DMF) years and were predominantly female (72.0% FTY; 69.6% DMF) and white (86.3% FTY; 82.2% DMF). At ≤24 months, 93 (34.3%) and 161 (47.1%) discontinued FTY and DMF, respectively, with an unadjusted odds ratio (OR) of 1.70 (1.23–2.37, p  = 0.002), or 1.69 (1.16–2.46, p  = 0.006) for the doubly robust propensity score weighted estimator. Primary reason for discontinuation was AEs, which were less likely for FTY 46 (17.0%) compared to DMF 82 (24.0%) (OR 1.54, 1.03–2.31, p  = 0.035). Discontinuation due to disease activity (FTY (10%) DMF (11.1%); OR 1.13, 0.67–1.90, p  = 0.647) and breakthrough disease activity, regardless of discontinuation (FTY (34.7%) DMF (33.6%); OR 0.95, 0.68–1.34, p  = 0.783), were similar. Conclusions: The odds of discontinuation were less for FTY than DMF, and were driven by AEs for both drugs.